Pemanfaatan Limbah Organik Menjadi Produk Bahan Bakar Briket - Kusnarta, I Gusti Made; Zinnur'ain; Zakirah, Awanis; Mardianti; Astuti, Dewi; Amni, Diya’ Islamiati; Sari, Diah Mala; Bararah, Zakiyyatul; Satriawan, Muhammad; Alghifari, Alif Satya; Januardi, Azril (Universitas Mataram, 2025)
Students of KKN PMD Universitas Mataram held a demonstration of the utilization of organic waste which aims to reduce the amount of organic waste and provide alternative energy sources for the people of Pelangan Village, especially Puwaringan Hamlet. Agricultural waste such as rice husks and coconut shells which have been underutilized are processed into Briquettes as environmentally friendly fuel. The activity method includes identifying problems, finding solutions, and demonstrating Briquette making. The Briquette making process includes drying raw materials, charring, refining, mixing with adhesives, molding, and final drying. The results of the activity showed that the community was very enthusiastic in learning and interested in trying this new technology. In addition, the community began to consider Briquette production as a new business opportunity to improve their economic welfare. With this activity, it is hoped that public awareness of waste management will increase, while encouraging the use of renewable energy in a sustainable manner